Burden of Tuberculosis in females in rural area at a tertiary care centre - Yadav, Sarita; Goel, Shikha; Agrawal, Anand (Asian Journal of Medical Sciences, 2015)
Backgroud: Tuberculosis (TB) is the second leading cause of death worldwide amongst communicable diseases. TB kills approximately 1 million women every year and is responsible for more deaths in women in the reproductive age group. Aims and Objectives: The present study was aimed to delineate the burden of disease in women in rural area. Results: High incidence of TB is reported in females of reproductive age group. Conclusion: Routine TB screening should be incorporated into maternal and child health programs in countries where TB is endemic. Revised National Tuberculosis Control Program (RNTCP) should mobilise interventions at rural level to eliminate stigma and ultimately eliminate TB’s impact on women. Asian Journal of Medical Sciences Vol.7(1) 2015 108-110